Gestational trophoblastic disease findings of a five year period retrospective audit - Sagoo, Balvinder; Abulhassan, Nashwa (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Background: To identify the incidence, characteristics and symptoms of women diagnosed with gestational trophoblastic disease (GTD) in an early pregnancy unit in Slough, Uk. To assess the accuracy of ultrasound diagnosis in detecting GTD in our early pregnancy unit at Wexham Park Hospital. To evaluate the management of patients diagnosed with GTD compared to RCOG guidelines. Methods: Qualitative observational study, retrospective audit over a five year period. Frimley Health NHS Foundation Trust January 2010 – December 2014. Women diagnosed with GTD based on ultrasound or histological diagnosis. Patients diagnosed with GTD/ GTN were identified through registration with Charing Cross Hospital (CXH), screening centre for GTD. Data was collected from CXH, WPH information databases: CRIS, PACs and ICE. Data was analysed and results presented. Results: Over a 5 year period, 53 out of 21,995 pregnant patients were diagnosed with GTD (Incidence of 1 in 415) 62% of patients diagnosed with GTD were of white ethnic origin. Accuracy of ultrasound diagnosis in our unit was 40%. Conclusions: We found a high incidence of GTD in the non-Asian population (1 in 415). Most patients who had been diagnosed with GTD on ultrasound were in the first trimester. Accuracy of ultrasound diagnosis is 40 % over a 5 year audit period. The main ultrasound findings of GTD were cystic changes and mixed echogenic echoes. Patients who were undiagnosed on ultrasound but had histological diagnosis of GTD had missed miscarriage as the predominant ultrasound diagnosis. Most patients were registered with the screening centre within six weeks of the histological diagnosis.